Study on oil fouling in a double pipe heat exchanger with mitigation by a surfactant. Issue 5 (14th April 2020) - Hasan, Basim O.; Majdi, Hasan Sh; Hathal, Mustafa M.
Abstract: Fouling of oils on heat exchanger surfaces and pipelines is a common problem in a variety of industrial applications. This is because the oil deposits on the heat transfer surface causes an increase in pressure drop and a decrease in heat exchanger efficiency. In the current work, oil fouling in double pipe heat exchanger was investigated and mitigated using a surface‐active agent for the flow of a dispersion fluid containing different dispersed oil fractions in water. The effect of the dispersed oil fraction (5%vol and 10%vol) and temperature (35°C‐55°C) on the oil fouling rate was studied and discussed under turbulent flow conditions for both hot and cold fluids. Different amounts of alkylbenzene sulfonate as a surfactant were added to reduce the fouling rate under turbulent flow. It was found that the fouling thermal resistance ( R f ) increases when the fluid temperature decreases. The higher the dispersed oil fraction, the higher the R f for all temperatures due to higher oil deposition. Addition of 0.2%vol to 0.5%vol of alkylbenzene sulfonate caused an appreciable reduction in R f depending on oil fraction and Reynolds number. The mitigation percent was higher for a lower Reynolds number, reaching up to 96%.